(untitled) (Bangladesh Critical Care Journal, 2026)
Transverse myelitis is an extremely rare manifestation of central nervous system tuberculosis, involving 1 or more vertebral segments of the spinal cord. However, it may extend to involve 3 or more segments of the cord, which would then be designated as longitudinally extensive transverse myelitis (LETM). Tuberculous transverse myelitis may occur in isolation or in association with adjacent meningitis. Here, we report a 15-year-old girl who was referred with rapid onset of quadriparesis with altered level of consciousness and showed LETM on spinal MRI. This report indicates that spinal tuberculosis should be considered as a differential diagnosis of LETM, especially in endemic areas. Bangladesh Crit Care J March 2026; 14 (1): 59-64